What is New and Innovative in Emergency Neurosurgery? Emerging Diagnostic Technologies Provide Better Care and Influence Outcome: A Specialist Review - Zisakis, Athanasios K.; Varsos, Vassilios; Exadaktylos, Aristomenis (Emergency Medicine International, 2013)
The development of emergency medical services and especially neurosurgical emergencies during recent decades has necessitated the development of novel tools. Although the gadgets that the neurosurgeon uses today in emergencies give him important help in diagnosis and treatment, we still need new technology, which has rapidly developed. This review presents the latest diagnostic tools, which offer precious help in everyday emergency neurosurgery practice. New ultrasound devices make the diagnosis of haematomas easier. In stroke, the introduction of noninvasive new gadgets aims to provide better treatment to the patient. Finally, the entire development of computed tomography and progress in radiology have resulted in innovative CT scans and angiographic devices that advance the diagnosis, treatment, and outcome of the patent. The pressure on physicians to be quick and effective and to avoid any misjudgement of the patient has been transferred to the technology, with the emphasis on developing new systems that will provide our patients with a better outcome and quality of life.